Clinical and prognostic outcomes of colposcopy-guided LEEP versus cold knife conization in the management of cervical intraepithelial neoplasia - Jin, Fengying; Wang, Lingling; Su, Zhan (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the clinical effectiveness and prognostic outcomes of colposcopy-guided LEEP compared with cold knife conization (CKC) in the treatment of cervical intraepithelial neoplasia (CIN).Methods124 patients with CIN in our hospital from January 2022 to December 2023 were chosen and classified into the control group (62 cases) and the observation group (62 cases) according to the therapeutic schedule. The observation group was treated with colposcopy combined with LEEP, while the control group underwent conventional cold knife conization (CKC). The clinical effect, surgical indicators, complications were compared. The control group underwent LEEP without colposcopic guidance, following standard clinical protocol.ResultsThe efficacy of the observation group was markedly better than that of the control group (95.16% vs. 75.81%, χ² = 9.358, P = 0.002). The operative time (35.35 ± 2.81 vs. 56.92 ± 2.17 minutes), intraoperative blood loss (8.08 ± 0.27 vs. 16.03 ± 2.27 mL), vaginal bleeding time (7.76 ± 1.85 vs. 11.37 ± 2.45 days), and hospital stays (2.74 ± 0.97 vs. 6.73 ± 1.33 days) were all significantly shorter in the observation group (P < 0.001). The complication rate was also lower (6.45% vs. 20.97%, P = 0.019).ConclusionThe findings suggest that this combined therapy is not only more effective but may also improve pregnancy outcomes for patients, making it a promising option for clinical application.